Resiko Disfungsi Seksual Pada Wanita Menopause - Muchsin, Enur Nurhayati; Huda, Moch Maftuchul; Setyorini, Dwi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: Menopause is a natural phase in a woman's life, the end of the menstrual cycle, usually occurs between the ages of 45 and 55 years. caused by decreased estrogen and progesterone hormones, can cause various physical and psychological symptoms, including an increased risk of sexual dysfunction. Sexual dysfunction in menopausal women includes various aspects, such as decreased sexual desire, difficulty achieving orgasm, pain during intercourse (dyspareunia). The purpose of the study was to determine the Risk Profile of Sexual Dysfunction in Menopausal Women in Pelem Village, Pare District, Kediri Regency. Method: Quantitative descriptive research design, population and sample of 30 respondents, sampling technique used Total sampling. Research variables Risk Profile of Sexual Dysfunction in Menopausal Women, The study was conducted on December 15-30, 2025, using the FSFI (Female Sexual Function Index) questionnaire instrument. The results showed that almost all respondents had a risk of sexual dysfunction (76.7%). Conclusion: Menopausal women can experience the risk of sexual dysfunction influenced by age, occupation, duration of menopause and estrogen deficiency. Menopausal women can overcome menopause problems by improving themselves, learning from menopausal women, making peace and accepting menopause.